An in vitro investigation of the effects of urolithins A and B on low-density lipoprotein uptake and its regulatory genes - Shiva Ganjali; Maryam Matbou Riahi; Khadijeh Mahboobnia; Milad Iranshahy; Maciej Banach; Ali Jangjoo; Sorour Ashari; Zahra Tayarani-Najaran; Amirhossein Sahebkar (Archives of Medical Science, 2023)
Introduction This study aimed to evaluate the possible role of urolithin A (UA) and urolithin B (UB) on the mRNA expression levels of LDL receptor (LDLR) and PSCK9 genes, and also of the uptake of LDL particles in HepG2 cells.